Toxicity, phytochemical screening and chemical composition of acalypha indica - Nurul Nadia binti Mohd Nazri (Kulliyyah of Allied Sciences, International Islamic University Malaysia, 2016)
Natural products such as herbs have been extensively explored due to its medicinal properties that exist within the plants. This study aimed to evaluate the chemical composition and phytochemical content of Acalypha indica dried plant and extract. It is also aimed to collect recent data in acute and subchronic toxicity study based on haematological, biochemistry and histological examinations on normal rats. The chemical composition analysis was conducted based on method adopted from Association of Official Analytical Chemist (AOAC) (2003) and calculation by difference. The phytochemical screening was performed according to standard method. In acute toxicity study, 24 Sprague Dawley rats aged 8 weeks were randomly divided into two groups, 6 animals per gender. The treated group was given a single dosage of 5,000 mg/kg body weight of dried A. indica extract while control group received water vehicle and observed for 14 days. In subchronic toxicity study, 48 Sprague Dawley rats aged 8 weeks were randomly divided into four groups, 6 animals per gender. A control group received water vehicle while three treated groups received the extract at dosage of 100, 200 and 300 mg/kg body weight of dried A. indica extract. The sample was administered daily by oral gavage for 90 days. The samples used for chemical analysis and phytochemical screening were dried root, dried leaves, dried stem, dried whole plant and the whole plant extract. The chemical composition analysis showed that the dried leaves contained the significant moisture (9.50+0.02%), ash (12.83+0.03%) and protein (23.98+0.10%) content as compared to other samples (p<0.05). The root contained the most significant carbohydrate (80.13+0.22%), crude fibre (42.05+0.36%) and gross energy (347.50+0.50Kcal/100g) content as compared to other samples (p<0.05) while the root had the lowest water activity (0.51+0.00 Aw) as compared to other samples (p<0.05). The phytochemical screening revealed the absence of alkaloids in all samples while saponins presence in whole plant extract and tannins in the dried whole plant, whole plant extract and dried leaves. The triterpenes and steroid were presence in all samples except the whole plant extract, while flavonoid was presence in all samples analysed. In acute toxicity study, the blood and histopathological result showed no sign of toxicity. In subchronic toxicity study, histopathology slide of the kidney, heart and liver revealed certain cellular damage in both control and treatment groups and it is suggested due to infection and stressful environment. However, the treatment groups showed better cell condition. Based on these results, it can be concluded that A. indica did not show any toxic effect in acute and subchronic toxicity study. LD50 for A. indica extract was more than 5000mg/kg body weight. Thus, this study proved that A. indica extract might be safe for human consumption when administered orally.